2016
DOI: 10.1016/j.eurpsy.2016.01.1016
|View full text |Cite
|
Sign up to set email alerts
|

Personality dimensions and drug of choice: A descriptive study using Cloninger's temperament and character inventory revised

Abstract: Personality dimensions related with drug use are novelty seeking, impulsivity and harm avoidance. Studies predicting drug of choice over personality variables are controversial.ObjectiveTo describe personality profile of drug users in relation to substance of choice.AimsTo know personality dimension differences according to drug used.MethodsCloninger's TCI-R was administered to 218 patients in a dual diagnosis unit.SPSS was applied.ResultsOf the patients, 33.94% had personality disorder. Principal substances u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…NS and HA are associated with higher risk of substance abuse 17 , 19 . For example, those who had stimulant abuse reported higher scores of NS, while those who had opioid and hypnotics abuse reported higher scores of HA 20 . In addition, both human and rodent studies demonstrated that high novelty seeking can predict an earlier beginning stage of drug abuse and a transition to compulsive drug use and relapse 21 .…”
Section: Introductionmentioning
confidence: 99%
“…NS and HA are associated with higher risk of substance abuse 17 , 19 . For example, those who had stimulant abuse reported higher scores of NS, while those who had opioid and hypnotics abuse reported higher scores of HA 20 . In addition, both human and rodent studies demonstrated that high novelty seeking can predict an earlier beginning stage of drug abuse and a transition to compulsive drug use and relapse 21 .…”
Section: Introductionmentioning
confidence: 99%